(untitled) (Texas Journal of Agriculture and Biological Sciences, 2022)
Although the idea of micro–organism such as bacteria in standard is dangerous to humans, A quantity of its species are taken into consideration to be of superb cost and safety, especially in organic therapy, including the institution Bacteria Probiotics. Lactobacillus salivarius is one of the maximum fundamental forms of bacteria which can be innocent to people and which may also play a main position in their bioremediation potential in general. Moreover, Lactobacillus salivarius was identified by traditional methods using MRS agar selective medium, then by biochemical methods using the VITEK 2 method. Finally, Lactobacillus salivarius was confirmed using Multi Sequencing (MLST) and Biofilm technique. The main objective of this research is to isolate and characterize the novel bacterium salivarius Lacto from Greek yogurt and their ability for biological assay and for study to determine the effect of bacteriocin, which is secreted by these bacteria, and to study the extent to which these by-products to reduce environmental pollution by removing heavy metals from various environmental media by these products.